Nurturing the next generation: a reflection on the BANCC conference by student attendees. (2nd November 2022) - Bladen, Siobhan; Brooks, Jorji C; Gray, Nicola; Tunstall, Charli; Lotto, Robyn
Abstract : Following the notable success of the supported student placements at this year's British Association of Nusing in Cardiovascular Care conference, the initiative will be expanded on next year, with a focus on early-career nurses. In this article, the students and their mentor reflect on the conference.